Exploring the Benefits of Social Media in Supporting Sustainable Hiking Tourism in Puthuk Sempu, Indonesia - Faturrohman Dwi Alimin; Dhiyan Septa Wihara; Tatik Mulyati (Journal of Digital Business and Innovation Management, 2026)
This study aims to explore the benefits of social media in supporting the implementation of sustainable tourism in the Puthuk Sempu hiking tourism area. This study aims to explore the role of social media in the sustainability of Puthuk Sempu hiking tourism based on the location of Puthuk Sempu hiking tourism between two other hiking tourism, but Puthuk Sempu hiking tourism has been able to survive until now. This study uses qualitative methods through observation, interviews, and documentation to obtain narrative data. The results show that social media has been proven to support promotion, communication, and digital mapping. This study also emphasizes the importance of integrating local resources and simple digital utilization to maintain the sustainability of hiking tourism, by showing the correlation between obstacles and supporting factors for the sustainability of Puthuk Sempu hiking tourism.